2021
DOI: 10.1080/09645292.2021.1882391
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of overqualification: evidence from the early career of graduates

Abstract: This study analyses the persistence and true state dependence of overqualification, i.e. a mismatch between workers' qualifications and their jobs' educational requirements. Employing individual-level panel data for Germany, we find that overqualification is highly persistent among university graduates over the first ten years of their career cycle. Accounting for unobserved heterogeneity, results from dynamic random-effects probit models suggest that a moderate share of the persistence can be attributed to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Policy interventions aimed at enhancing job mobility, such as skill recognition programs and gaining work experience before graduation, can be effective in addressing education-occupation mismatch and reducing labor market imbalances (Montt, 2017). Additionally, as we showed in this paper, pursuing a Master’s program can contribute to mitigating horizontal skill mismatch (Erdsiek, 2021).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Policy interventions aimed at enhancing job mobility, such as skill recognition programs and gaining work experience before graduation, can be effective in addressing education-occupation mismatch and reducing labor market imbalances (Montt, 2017). Additionally, as we showed in this paper, pursuing a Master’s program can contribute to mitigating horizontal skill mismatch (Erdsiek, 2021).…”
Section: Discussionmentioning
confidence: 77%
“…Our findings show that attending a Educationoccupation mismatch college field that does not build on a previous high school track increases the risk of horizontal mismatch at the first job after graduation. Moreover, graduates that are mismatched at the first job also seem more likely to remain mismatched at the workplace five years following graduation, suggesting that the first job might determine the graduate's subsequent professional career (Erdsiek, 2021). Another key finding refers to vertical mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the overqualification literature focuses on age and immigrant status, creating a need over overqualification research with a focus on other categories of vulnerable workers including those with a disability (e.g., Rafferty, 2020;Erdogan, Bauer, Peiró, & Truxillo, 2011). At a macro level, discrimination driven employee job mismatches lead to productivity losses (Erdsiek, 2021). At a micro level, overqualified employees are underpaid (Banerjee, Verma, & Zhang, 2018) and may experience reduced wellbeing (Hilbrecht, Smale,, & Mock, 2017).…”
Section: Over Qualification and Workplace Discriminationmentioning
confidence: 99%
“…A worker is considered to be overeducated if someone education level is higher than that required to adequately perform a specific job (McGuinness, 2006). The evidence indicates that young workers entering the labour market for the first time are the most affected (Meroni and Vera-Toscano, 2017; Erdsiek, 2021) and that the incidence level falls as their age and experience increases. However, research has shown that this evidence cannot be generalized to all workers.…”
Section: Introductionmentioning
confidence: 99%